2002
DOI: 10.1091/mbc.e02-04-0196
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-dependent Subcellular Relocalization of the Acyl Chain Desaturase in Yeast

Abstract: The degree of acyl chain desaturation of membrane lipids is a critical determinant of membrane fluidity. Temperature-sensitive mutants of the single essential acyl chain desaturase, Ole1p, of yeast have previously been isolated in screens for mitochondrial inheritance mutants (Stewart, L.C., and Yaffe, M.P. ). J. Cell Biol. 115, 1249 -1257. We now report that the mutant desaturase relocalizes from its uniform ER distribution to a more punctuate localization at the cell periphery upon inactivation of the enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 54 publications
5
17
0
Order By: Relevance
“…yeast, Ole1p (52,53,62); accordingly, overexpression of OLE1 under control of the strong GAL1/10 promoter neither stimulated desaturation, nor did it enhance cell death of the quadruple mutant (data not shown), consistent with the notion of multiple levels of control of desaturase activity in yeast (53). Second, saturated FA supplementation to mutants unable to synthesize TAG had no apparent effect on viability, in yeast.…”
Section: Strainsupporting
confidence: 56%
“…yeast, Ole1p (52,53,62); accordingly, overexpression of OLE1 under control of the strong GAL1/10 promoter neither stimulated desaturation, nor did it enhance cell death of the quadruple mutant (data not shown), consistent with the notion of multiple levels of control of desaturase activity in yeast (53). Second, saturated FA supplementation to mutants unable to synthesize TAG had no apparent effect on viability, in yeast.…”
Section: Strainsupporting
confidence: 56%
“…All these proteins are described as ER-localized enzymes (7,39,40). The reason for a higher proportion of mislocalized sphingolipid enzymes was not due to the expression from an episomal plasmid but may rather reflect particular sensitivity of these enzymes to C-terminal modification and/or interference Endoplasmic reticulum (92) a ALG9, AQY1, ARE1, ARE2, AUR1, AYR1*, BOS1*, CHO1, CHO2, COX10*, CSG2*, CSR1*, CYB5, DGA1*, DPL1, DPP1*, EHT1*, ELO1, EPT1*, ERG1*, ERG2*, ERG24*, ERG25*, ERG26, ERG27*, ERG3*, ERG4, ERG5, ERG6*, ERG7*, ERG9*, EUG1*, FAA1*, FAA4*, FAT1*, FEN1, FEN2, FPS1, GAA1*, GOG5, GPI11, GPI2, GPI8, GSF2, GUP1, HMG1*, INP54*, IRE1, LCB2, LPP1*, MEC1, NCP1, NCR1, OLE1, OPI3*, PAU7*, PHO86, PIK1*, PIS1*, PLB1*, PLB2*, PTC2*, RVS161*, SAC1*, SCS7*, SEC14*, SEC22*, SLA1*, SLC1*, SPC1, STE14, SUR2, SUR4, TIP1, TSC10*, YBR204C*, YDC1*, YDL015C*, YDL193W*, YDR018C*, YIL011W, YIM1*, YJU3*, YKL174C*, YKR003W*, YLR343W, YOL132W*, YOR059C*, LCB1, YJU3*, NVJ1, YDL015C* Lipid droplets (23) AYR1*, DGA1*, EHT1*, ERG1*, ERG27*, ERG6*, ERG7*, FAA4*, FAT1*, PDR16*, SLC1*, TGL1, TGL3, YBR042C, YBR204C*, YDL193W*, YDR018C*, YIM1*, YJU3*, YKR046C, YKR089C, YOR059C*, YOR081C Peroxisomes (17) ACS1, DCI1*, FAA2*, MDH3*, PEX10, PEX11, PEX13, PEX14, PEX17*, PEX19*, PEX2*, PEX3, PEX4, PEX5*, POT1, POX1, SPS19* Plasma membrane (14) ALR1*, ERG13*, FAA1*, FAA3, GIT1*, PDR16*, PDR17*, SNQ2, TSC10*, VHT1*, YJL145W*, YLL012W, YMR210W*, YOR009W* Mitochondria (27) AAD10, ACP1, AGP2, BIO2, CEM1*, COQ1, COX10*, COX4, CPT1, CRC1, CYB2, ECM1, ERG13*, GUT1, HEM1, PGS1, PPT2*, PSD1, RAM1*, RVS167, SCS3, TES1, TGL2, YAP1, YBR159W*, YDR531W, YPR140W Vacuole, membrane (7) ALR1*, AST2*, DPP1*, PIB1, PIB2, VPH1, YBR161W* Vacuole, lumen (5) GIT1*, PKA3*, SUR1*, YIL005W, YOR009W* Nucleus, lumen (56) ACS2, ADA2*, ALD2, ARD1*, BDF1, BET2*, BET4, CDC43*, DCI1*, ERG10, ERG13*, FMS1*, GCN5, GDS1, HAP2, HAP5, HDA1, HHF1, HHT1, HHT2, HTA3*, IML3*, INO4*, MRS6*, MUQ1*, NAT1, NDD1*, PGD1*, PIP2*, PKA3*, QRI2, RAD61, RAM2*, REX3, RFA2*, RFA3*, ROX1, RPD3*, RTT105, SCM3, SEC21, SKN7, SPO12, THI3, TOR2*, TUP1*, YCR072C*, YGL144C*, YGR198W*, YHR046C*, YJR107W*, YKL091C, YLR323C, YMR192W, YNL086W*, YOL054W Nucleus, nucleolus (5) ADA2*, HTA3*, IML3*, RER2*, YCR072C* Nucleus, envelope (6) ADR1, NDD1*, NUP53, OPI1, PCT1, YPC1* Vesicles (55) APG7*, APL2*, AQY2, AST2*, BET1, BOS1*, CDC48*, CSG2*, DPP1*, ERG2*, ERG20, ERG24*, ERG25*, ERG3*, ERG9*, EUG1*, FAA1*, GAA1*, GIT1*, GTS1, HES1*, HFA1*, HMG1*, INP54*, KES1*, LPP1*, OPI3*, PAU7*, PDR5*, PIS1*, PKA3*, PLB1*, PLB2*, PLB3*, PPT2*, PTC2*, RER2*, SCS7*, SEC22*, SUR1*, TSC10*, VHT1*, VPS4*, YBR108W*, YBR161W*, YDC1*, YDL015C*, YGR198W*, YJL072C, YKL174C*, YKR003W*, YKT6, YOL132W*, YOR009W*, YPC1* Golgi (7) BET3*, EPT1*, GDA1, PIK1*, PIS1*, SAC1*, SEC14* Cytoskeleton (7) SAC6*, SLA1*, SRV2*, YGR136W, YSC84*, YDR532C*, ZTA1* Others (8) SEC2*, VPS24, CEM1*, GCD7, HNM1, STT4, TOR1, YDR541C* Cytoplasm (177) AAD6, AAH1, ACB1, ACF2, ACH1, ALD6, APG1, APG12, APG13, APG16, APG7*, APG9, APL2*, ARD1*, AST1, AST2*, AUT7, BET2*, BET3*, B...…”
Section: Overexpression Of Gfp Fusions Results In Stablementioning
confidence: 99%
“…We have previously observed that a conditional variant of the Ole1 protein, Mdm2 ts (54), is reversibly sequestered within minutes into ER domains under restrictive conditions when the enzyme is unable to desaturate fatty acids. This relocalization process is suppressed by unsaturated fatty acid supplementation (55), clearly demonstrating that localization of this lipidmetabolizing enzyme is strongly dependent on its lipid environment, which may become modified by its own enzymatic activity. Such a model would also explain how changes in the lipid profiles by altered growth conditions or mutations result in major rearrangements of membrane lipid compositions.…”
Section: Yeast Large Scale Gfp Localization Studymentioning
confidence: 93%
“…To determine the membrane association and topology of the GFP-tagged lipases, detergent and salt extractions and proteinase K protection experiments were performed essentially as previously described (47). Detergent and salt extractions of microsomal membranes (P13) were performed by incubating 50 g of the microsomal fraction with either 1% Triton X-100, 7% SDS, 1 M NaCl, or 0.1 M Na 2 CO 3 in lysis buffer A without protease inhibitors for 30 min on ice.…”
Section: Methodsmentioning
confidence: 99%